Development of the discrimination of spatial phase in infancy. - Braddick, O; Atkinson, J; Wattam-Bell, JR (1986)
The ability to discriminate grating patterns, containing the same spatial frequency components but in different phase relationships, has been studied in infants by comparing looking times following habituation to one pattern. The performance of 1-month-olds was compared with that of 2/3-month-old infants. Both age groups could discriminate a set of components in square-wave-phase (fundamental 0.18 c/deg) from components of the same amplitude combined in random phase. However, these compounds differ in peak-to-trough contrast, which infants of both ages could discriminate even for a constant waveform. When contrast was randomized from presentation to presentation, the older group still demonstrated discrimination, implying that they were sensitive to the pattern differences, but the younger group did not. The younger group also failed to demonstrate discrimination between the two waveforms when they were of fixed, matched, peak-to-trough contrast, indicating that the previous absence of discrimination was not simply due to distraction by the contrast variations. We conclude that 1-month-olds are insensitive to the configuration of these compound grating patterns even when they are capable of detecting their components. This loss of spatial information has some analogies with adult peripheral and amblyopic vision. Like other aspects of vision, it shows striking development between 1 and 3 months of age.